Bureaucratic reform in irrigation: a review of four case studies - Suhardiman, Diana; Giordano, Mark; Rap, Edwin; Wegerich, Kai (2014)
Poor performance of government-managed irrigation systems persists globally. This paper argues that addressing performance requires not simply more investment or different policy approaches, but reform of the bureaucracies responsible for irrigation management. Based on reform experiences in The Philippines, Mexico, Indonesia, and Uzbekistan, we argue that irrigation (policy) reform cannot be treated in isolation from the overall functioning of